Occupational Stress and Work Engagement: The Psychological Capital as A Moderator - Atti, Liqaa Mutter; Al-Maatoq, Marwa; Amanah, Ahmed (Technium Social Sciences Journal, 2024)
This study aims to examine how job stress and interactions at work are affected, as well as how psychological capital acts as a moderator. This research is descriptive, and it falls within the category of applied research in terms of its goal. The research's statistical population comprised 450 personnel and professionals from Basra Petrochemical Industry General Company. 207 people made up the sample size according to Cochran's formula, and a straightforward random sampling technique chose the sample members. The findings indicated that work interactions negatively influence job stress. Psychological capital moderates the link between occupational stress and psychological capital.